Prevalence of age-related macular degeneration in the Republic of Ireland - Akuffo, Kwadwo Owusu (Br J Ophthalmol, 2015)
BACKGROUND: Age-related macular degeneration (AMD) remains the most common cause of visual loss among subjects over 50 years of age in the developed world. The Irish Longitudinal study on Ageing (TILDA) is a population-based study of subjects aged 50 years or older, designed to investigate factors that influence ageing, and has enabled this investigation of the prevalence of AMD in the Republic of Ireland (ROI). METHODS: Data collected from a nationally representative sample of community-living older adults aged 50 years and over in ROI over the period November 2009 to July 2011. 5035 participants attended the TILDA health centre for assessment. Retinal photographs were obtained in 4859 of these participants. Retinal grading was performed in a masked fashion using a modified version of the International Classification and Grading System for AMD. RESULTS: Adjusting for lower response rates among older subjects, the estimated overall prevalence of any AMD was 7.2% (95% CI 6.5% to 7.9%) in the population aged 50 years or older. The estimated prevalence of early AMD was 6.6% (95% CI 5.9% to 7.3%), and the estimated prevalence of late AMD was 0.6% (95% CI 0.4% to 0.8%). Statistically significant associations with AMD included increasing age and family history of the condition. CONCLUSIONS: This is the first study to provide prevalence estimates of AMD in ROI and will inform eye care professionals and policymakers involved in the delivery and planning of care for those afflicted with this condition.